The performance of lap splices in RC beams under inelastic reversed cyclic loading. (August 2018) - Najafgholipour, M.A.; Dehghan, S.M.; Khani, M.; Heidari, A.
Abstract: A number of design codes such as ACI 318-14 have prohibited the use of lap splices in critical zones of special moment frames where flexural yielding is anticipated. This restriction is due to the unreliable performance of lap splices under cyclic loading. This article is concerned with the flexural performance of RC beams with lap splices under reversed quasi-static cyclic loading. For the calculation of lap splice length two procedures were adopted here; i.e. conventional design procedure recommended in ACI 318-14 and modified splice length which assumes 1.25 f y in design relations instead of the nominal yield strength. For this purpose, a total of nine full-scale RC beams with different splice and reinforcement configurations for two grades of steel were designed and fabricated. Four-point bending tests were carried out on test specimens to evaluate the performance of lap splices under pure bending. Test results indicated that the specimen with splice designed according to ACI318-14 provisions could not survive reverse cyclic loading up to flexural failure. However, the specimens with a modified splice length were able to survive cyclic loading with adequate flexural ductility.